Dose-intensified bi-weekly temozolomide in patients with asymptomatic brain metastases from malignant melanoma: a phase II DeCOG/ADO study - Schadendorf, Dirk; Ugurel, Selma; Figl, Adina (Annals of oncology, 2006)
Background: Temozolomide has shown some efficacy in metastatic melanoma and recently received extended approval to treat brain tumours. The purpose of this study was to test a dose-intensified regimen of temozolomide in melanoma patients with brain metastases in a prospective, open-label, multicentre phase II trial. Patients and methods: Forty-five patients with asymptomatic brain metastases from melanoma were stratified into arm A (no prior chemotherapy; n = 21) and arm B (previous chemotherapy; n = 24). Patients received oral temozolomide either 150 mg/m2/day (arm A) or 125 mg/m2/day (arm B), days 1-7 and 15-21, every 28 days. The primary study end point was objective response, and secondary end points were overall survival and safety. Results: Two patients (4.4%) achieved a partial response (PR) in brain metastases (one in each arm), one of them (2.2%) also showing a PR in extracerebral disease. An additional five patients (11.1%; two in arm A, three in arm B) showed disease stabilisation (SD) in brain and other sites. However, 82% revealed progressive disease (PD) already evident 8 weeks after therapy initiation. Median survival time from therapy onset was 3.5 months (range 0.7-8.3; arm B) and 4.3 months (range 1.6-11.8; arm A), P = 0.43. Dose modifications and prolongations of therapy cycles due to toxicity were required in 20% of patients. Grade 3/4 toxicity was observed in one patient only (2.2%). Conclusions: Oral administration of temozolomide given bi-weekly is well-tolerated in melanoma patients with cerebral involvement. However, the efficacy is limited, with lower than 5% objective responses observed in brain and extracerebral metastases.
Elektronische Reproduktion der Druckausgabe
Gesehen am 05.02.2021